Clay Minerals in the Soils of South Kheri Forests, Uttar Pradesh - Banerjee, S. P.; Mathur, K. C.; Prasad, K. G.; Raina, A. K. (Indian Forester, 1989)
X-ray diffraction of selected soil clay of South Kheri forests of Uttar Pradesh brings out kaolinite as the dominant silicate mineral, both at the surface as well as the subsurface of all the pedons. In addition, small amounts of goethite, gibbsite and integrated micaceous minerals are also identified in the clay fractions. An occurrence of some vermiculite only in the three pedons under natural sal (Shorea robusta), which decreased at the subsurface, may perhaps be a peculiar coincidence only as no tangible explanation exists.